Social capital and idiosyncratic return volatility - Hasan, Mostafa; Habib, A. (Sage Publications, 2017)
We examine whether regional social capital has any impact on idiosyncratic return volatility. Using US data, we find that firms headquartered in high social capital counties exhibit significantly lower idiosyncratic return volatility. This effect is more pronounced in the presence of financial reporting quality and corporate social responsibility. When we estimate the direct and indirect effects of social capital, our study reveals that the direct effect of social capital captures around 80% of the total effect. These findings suggest that firm-specific variables do not explain all of a firm’s idiosyncratic return volatility, but regional social capital also plays a role.